2017
DOI: 10.2147/opth.s109708
|View full text |Cite
|
Sign up to set email alerts
|

The Sensimed Triggerfish contact lens sensor: efficacy, safety, and patient perspectives

Abstract: Intraocular pressure, a major modifiable risk factor for glaucoma, has been shown to fluctuate throughout the day in patients with glaucoma. The detection and measurement of this fluctuation may help guide the clinical management of glaucomatous individuals. The Sensimed Triggerfish contact lens sensor (CLS), which has recently gained approval for marketing in the USA, is designed to detect intraocular pressure-related changes in an eye over a 24-hour period. This review will provide an overview of the Trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 20 publications
0
71
0
2
Order By: Relevance
“…Previous work has shown that the radius of curvature of the cornea changes as IOP changes [12] [13]. Based on this information, a 250um thick polydimethylsiloxane (PDMS) soft contact lens was manufactured with an embedded 100 um wide by 100 um thick microfluidic channel ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that the radius of curvature of the cornea changes as IOP changes [12] [13]. Based on this information, a 250um thick polydimethylsiloxane (PDMS) soft contact lens was manufactured with an embedded 100 um wide by 100 um thick microfluidic channel ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a continuous monitoring contact system, the Sensimed Triggerfish contact lens, has been approved for marketing. This device is designed to detect changes in eye shape induced by changes in intraocular pressure, but appears to provide data on relative changes in intraocular pressure rather than absolute intraocular pressure [12].…”
mentioning
confidence: 99%
“…Considering the aforementioned features and relative ease of fitting the sensor, its utilization could bring valuable information into discussion on the ABP and IOP relationship. However, its broad application is currently limited by the high cost, which is estimated at $700 USD per one 24 h measurement [40].…”
Section: Perspectives -24 Hour Ocular Volume Monitoringmentioning
confidence: 99%
“…This device can only measure relative changes rather than determine absolute pressure. 31 There are currently many new intraocular sensor devices in development [32][33][34] and if any of these are proven to be accurate and safe, reliable continuous IOP monitoring for many patients may soon become a reality.…”
Section: Q: What Future Developments Can We Look Forward To In 2018?mentioning
confidence: 99%